Numerical Simulation on Cutting and Fracturing of Rock Plate with One Side Fixed and Three Sides Free - Zhenguo Lu; Qingliang Zeng; Zhaosheng Meng; Zhiwen Wang; Guanshun Gao (Advances in Materials Science and Engineering)
Conical pick is a rock cutting tool that is commonly used in roadway driving. Pick wear frequently happens in the course of breaking hard rock. The current paper shows a new method to solve the problem of pick wear. The rock is preslit with the saw blade and then broken by the conical pick. In order to study the cutting force and features of rock fragment, the numerical model is built between rock plate and conical pick. And element erosion is added in the code to obtain the fracture result. The rock plate cutting testbed is made to testify the correctness of numerical simulation. The width, height, and thickness of the rock plate, as well as cutting angle and cutting position, which influence cutting force and rock fracture are studied. According to the results, there exist exponential relationships between cutting force and width and thickness of rock plate. In addition, a linear relationship is found between the cutting force and the height of rock plate. Furthermore, both the cutting angle and cutting depth have an influence on cutting force. In particular, the factors of thickness and height or rock plate have the most obvious influence on cutting force. It is proven that what is beneficial to rock fracture is higher height and lower thickness of rock plate.